Factors influencing tax compliance behavior among the self-employed in Nigeria - Abdullahi, Umar Mohammed (2017)
The objective of the study was to investigate factors influencing tax compliance behavior among the self-employed in Nigeria. The level of tax noncompliance in Nigeria is unusually high. Some authorities have described the level of noncompliance in the country as one of the highest in the world. This research was designed as a mixed method whereby the research questions were answered through a mixture of qualitative and quantitative methodology. The qualitative study was designed as intensive interviews with a sample of thirty-two self-employed in the study area, Abuja, Nigeria. The quantitative study was designed as a questionnaire survey of 360 self-employed taxpayers in Nigeria’s capital city of Abuja. Nine variables were investigated to determine their influence on tax compliance behavior. The variables were: perceived public governance quality, socioeconomic condition, perceived audit effectiveness, perceived social norm, perceived citizen engagement, perceived tax service quality, perceived tax system complexity, tax fairness perception and attitude towards evasion. Data from the survey was analyzed using the Partial Least Square approach and the SmartPLS software. Results from the analysis produced a significant mediation effect of socioeconomic condition on the relationship between perceived public governance quality and tax compliance behavior. Perceived citizen engagement, perceived audit effectiveness, perceived social norm and perceived tax service quality were all found to have a significant positive relationship with tax compliance behavior. The study made good contributions to existing literature by introducing the mediating role of socioeconomic condition and also the construct of perceived audit effectiveness into tax compliance research. Finally, the study highlighted the implications of the findings for policy, methodology and theory. The policy recommendation emphasized the need for the Nigerian government to adopt the carrot and stick approach in influencing tax compliance behavior.